The Formulasi Lip Balm Dari Kandungan Minyak Rumput Laut Eucheuma Cottoni - Virna Agustina; Tiara Tiara; Andika Hidayat; Baizurah Abda Sabilah; Imra Imra (Jurnal Inovasi dan Kreativitas (JIKa), 2023)
Problems: The fishery potential that is often found in the waters of the city of Tarakan is Eucheuma cottonii seaweed. This type of seaweed is a potential fishery resource with high economic value. E cottonii seaweed is only sold in dry form and food processing, so the need for diversification of non-food products that can increase the selling value is higher. Purpose: The purpose of this study was to determine the formulation and characteristics of lip balm from Eucheuma cottonii seaweed. Methodology: The research was conducted in two stages, the first stage was the formulation and preparation of lip balm preparations and the second stage was the characterization of the lip balm formulations. Characterization includes smear test, organoleptic observation, homogeneity test, pH test, stability and melting point observation. Results/Findings: The results of this study showed that the pH measurement of seaweed lip balm preparations for each formula was 7.46 - 8.85. Based on the results of the homogeneity test the P1 formula showed the presence of coarse grains, the P2 formula showed medium and the P3 formula showed very fine grains. Based on the results of stability testing for each preparation, it showed that on days 0 and 7 it remained stable. However, the color faded during 14 and 21 days of observation at room temperature. Melt test of preparation P1 to 24 minutes, P2 to 27 minutes and P3 to 20 minutes.